Diagnóstico de las implicaciones de la modalidad híbrida distancia-virtual en estudiantes de la ESPAM MFL, durante la pandemia COVID-19 - Mera Giler, Melina Jacqueline (2022)
The objective of this Curricular Integration Work was to diagnose the implications of the Virtual Distance Hybrid modality in students of the ESPAM MFL, during the COVID-19 pandemic to guarantee the right to education where different activities were carried out for compliance of the specific objectives applying the survey technique, in addition to the deductive, inductive, analytical methods and the types of bibliographic and field research, likewise all the related contents of great relevance to the research problem were investigated, where different epigraphs that are the bibliographic support of the operative part of the work were highlighted. Among the first results obtained, is that during the pandemic students have experienced different feelings and emotions, highlighting concern and uncertainty in most of them, in addition to the fact that the survey applied reflects that 73.4% of students have had problems in their psychological health because of the current situation, as well as 44% have had problems in adapting to the change in the modality of studies Hybrid Distance-Virtual, and in other aspects such as economics where 92% have had effects either in their family or personal economy, for which an action plan is proposed as an ideal proposal for improving the quality of the training subsystem, integrating specific objectives and actions to solve the research problem.